Sejarah Lahirnya Gereja Kebangsaan di Minahasa - Changlie Harter Assa (Sekolah Tinggi Teologi Yerusalem Baru, Manado, 2021)
AbstractThis paper aims to show the existence of a national church in the land of Minahasa. This nationalist church was born from a group of Christian nationalists and Christian figures from the Minahasa. The result of the birth of the National Church was the establishment of KGPM, which was an independent church that was free from the shadows of Dutch colonialism. The national spirit of KGPM is manifested in its theme: Jesus Christ in Nationality, Nationality in Jesus Christ. The KGPM founders believed that Indonesian independence must also be in line with ecclesiastical independence. Concerning the national movement, the founders of KGPM were directly involved in Indonesia's independence. The movement performed together for the realization of independence from Dutch colonial The results of this paper, recommended to need for massive socialization of Christian leaders and organizations involved in the Indonesian independence processAbstrak Tulisan ini bertujuan untuk menunjukkan adanya gereja kebangsaan atau gereja yang menekankan landasan semangat nasionalisme di tanah Minahasa. Gereja kebangsaan ini lahir dari kelompok nasionalis Kristen dan tokoh-tokoh Kristen dari Minahasa. Hasil dari lahirnya gereja kebangsaan ialah berdirinya Kerapatan Gereja Protestan Minahasa yang adalah gereja mandiri yang lepas dari bayang-bayang kolonial Belanda. Semangat nasionalisme KGPM dinyatakan melalui tema: Yesus Kristus dalam Kebangsaan, Kebangsaan dalam Yesus Kristus. Pendiri KGPM yakin bahwa kemerdekaan Indonesia harus sejalan juga dengan kemerdekaan bergereja. Dalam kaitannya dengan pergerakan nasional, para pendiri KGPM ikut terlibat langsung terhadap pergerakan kemerdekaan bangsa Indonesia. Pergerakan dilakukan secara bersama-sama demi terwujudnya kemerdekaan dari kolonial Belanda. Hasil penulisan ini merekomendasikan perlunya sosialisasi secara masif akan adanya tokoh-tokoh Kristen dan organisasi-organisasi Kristen yang terlibat dalam proses kemerdekaan Indonesia